Portrait of Teachers Information and Communication Technology Master at SD Negeri 11 Indralaya, Ogan Ilir Regency - Idayana, Idayana; Harapan, Edi; Rahman, Andi (Yayasan Sembilan Pemuda Indonesia, 2023)
This research is qualitative research conducted to describe the condition of teachers' mastery of Information and Communication Technology (ICT) at SDN 11 Indralaya. The purpose of this study was to find out how much mastery teachers have in understanding and using Information and Communication Technology (ICT) at SD Negeri 11 Indralaya. The population in this study were teachers at SD Negeri 11 Indralaya, totaling 26 teachers and 5 staff of education staff. The results of this study revealed that of the 26 teachers on duty, 7 teachers were categorized as proficient in mastering ICT Technology, as many as 10 teachers were categorized as moderate in mastering ICT, and as many as 9 teachers were categorized as less proficient in mastering ICT Technology.